Fame and fortune, or just fun? A study on why people create content on video platforms. Issue 1 (14th August 2019) - Törhönen, Maria; Sjöblom, Max; Hassan, Lobna; Hamari, Juho
Abstract : Purpose: The purpose of this paper is to examine the motivations behind online video content creation on services such as YouTube and Twitch. These activities, performed by private individuals online, have become increasingly monetized and professionalised through the accessible tools provided by video sharing services, which has presented a noteworthy manifestation of the increasing merger of the work and leisure within digital environments and the emergence of a hybrid form of work and play, playbour. Design/methodology/approach: The data for the study were collected using an online survey of 377 video content creators and it was analysed via structural equation modelling. Findings: The findings of the study indicate that although the practice of video content creation is becoming more commercialised and professionalised, the extrinsic motivations, often associated with work (e.g. income, prestige), remain less significant drivers for content creation than intrinsic motivations (e.g. enjoyment, socialisation), which are associated with leisure activities. Originality/value: This study offers insight into how the authors have begun to reorganise the position in the new digital labour culture, where monotonous tasks are increasingly automated, allowing room for intrinsically driven playful labour to develop within the leisure activities.